A CORRELATION ANALYSIS OF ROCKY DESERTIFICATION GRADES, PLANT DIVERSITY AND SOIL FACTORS IN CENTRAL HUNAN OF CHINA - Peng, Jiqing; Cao, Fuxiang; Liu, Zhiming; Cao, Jiwu; Wu, Lichao; Li, Meng (Acta Scientiae et Intellectus, 2024)
Karst rocky desertification (RD) in central Hunan is a part of karst land degradation in southwest China. The change in grade of RD, or succession, has led to ecological degradation and seriously hindered socioeconomic development. RD succession is influenced by soil and vegetation. Taking central Hunan regions as a study area and using SPSS17.0 statistical software, we investigated the correlation between RD grades, plant diversity index and soil factors. Results showed that RD grades showed a significant positive correlation with soil organic matter (OM) and cation exchange capacity (CEC). The plant diversity index was positively correlated with the soil fertility index and showed a significant positive correlation with OM and available elements. Further analysis on the available elements showed that total plant diversity indices including Shannon-Wiener index H', Pielou index E and Simpson P had significant positive correlations with available magnesium (AMg). Total plant diversity indices E and P had significant positive correlations with available calcium (ACa). These conditions might have closely reflected the particular microhabitat types of RD regions. The correlation between RD grades, vegetation and soil factors suggested that the relationship of the three was co-evolutionary. To enhance RD control and treatment effectiveness, increasing the content of the ACa and AMg may be more impactful than increasing the content of OM in central Hunan.